(untitled) (Vietnam Journal of Community Medicine, 2025)
Introduction: The study aims to describe the practice regarding HIV/AIDS prevention of the pupils in Namkeung high school in Lao 2023 and its related factors. Methods: This cross-sectional survey was conducted through a self-administered questionnaire on all 357 pupils in Namkeung High School Results: The rate of pupils with good practice regarding HIV/AIDS prevention was 51.1%. This ’good practice’ was determined based on a set of criteria that included factors such as the number of sexual partners, sexual intercourse with high-risk groups, condom use, and substance use. Regarding associated factors, grade 12th pupils were 4.5 times more likely to practice HIV/AIDS prevention well than grade 10th pupils (72.7% vs. 37.2%; OR=4.5; 95% CI: 1.5-13.8; p<0.05). Pupils with good GPA were 3.4 times more likely to practice HIV/AIDS prevention than pupils with average GPA (64.9% vs. 35.1%; OR=3.4; 95% CI: 1.4- 8.7; p<0.05). Conclusions: The rate of pupils with good practice regarding HIV/AIDS was low. The study underscores the critical need for targeted education and early intervention. It recommends that school teachers should coordinate closely with parents in sex education in official lectures, extracurricular activities, classes, and club seminars. These strategies are crucial for improving prevention practices among high school pupils.